2009
DOI: 10.2989/ajar.2009.8.2.8.860
|View full text |Cite
|
Sign up to set email alerts
|

A model for understanding the relationship between stigma and healthcare-seeking behaviour among people living with HIV/AIDS in sub-Saharan Africa

Abstract: People living with HIV or AIDS (PLHIV) in sub-Saharan Africa sometimes have care-seeking behaviours that result in a suboptimal quality of life. This paper seeks to examine the role of stigma in the care-seeking behaviour of PLHIV. We hypothesise that stigma relates to the behaviour of PLHIV themselves and with societal reactions, including those of healthcare professionals. From a literature review, we identified the following as important correlates of care-seeking behavior: beliefs about pathways of HIV inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 63 publications
1
18
0
Order By: Relevance
“…Similar study was found in Botswana, in which Christian youth had more positive attitudes towards PLHA than those who have no religion [28]. In the lives of the sub-Saharan Africans, religion plays a major role and has been recognized as a factor which may alleviate the HIV/AIDS stigma [47]. In a study done in Ethiopia, being religious and religious service attendant was found to be the highest significant factor where respondents who attend the religious service at least once a week were 7 times more likely to have favorable attitude than those who didn't attend the religious service [44].…”
Section: Acceptance Attitudes Of Male Youthsupporting
confidence: 71%
“…Similar study was found in Botswana, in which Christian youth had more positive attitudes towards PLHA than those who have no religion [28]. In the lives of the sub-Saharan Africans, religion plays a major role and has been recognized as a factor which may alleviate the HIV/AIDS stigma [47]. In a study done in Ethiopia, being religious and religious service attendant was found to be the highest significant factor where respondents who attend the religious service at least once a week were 7 times more likely to have favorable attitude than those who didn't attend the religious service [44].…”
Section: Acceptance Attitudes Of Male Youthsupporting
confidence: 71%
“…The model adapted from the Precede portion of the (Green & Kreuter, 1999) Precede-Proceed model was helpful in understanding HIV-stigma related problems, coping mechanisms and care-seeking behaviors of PLWHA which can affect utilization of health-care institutions (Mbonu et al, 2009). This study shows that certain determining and moderating variables are important for PLWHA, in order for them to cope with HIV/AIDS and to make care choices.…”
Section: Resultsmentioning
confidence: 99%
“…Following prior research on stigma in relation to HIV/AIDS (Mbonu, Van Den Borne & De Vries, 2009), using an inductive approach from an extensive literature review in SubSaharan Africa, we adapted the Precede portion of the Precede-Proceed model (Green & Kreuter, 1999) as an explanatory model. The PRECEDE-PROCEED model provides a systematic approach for assessing quality-of-life of health and for designing, implementing, and evaluating health education and health promotion programs.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…(Gari et al, 2010;Anglewicz, et al, 2011;Stutterheim et al, 2011). In a previous study, we reviewed behavioral problems of PLWHA in Sub-Saharan Africa in seeking care, and argued that this is partly due to stigmatizing responses to PLWHA from health care professionals and society at large (Mbonu, Van den Borne, & De Vries, 2009). Given the negative impact of stigma on care seeking and the selective disclosure of a positive HIV-sero-status to close and trusted people, it is important to understand why HIV/AIDS attracts such a degree of negative reaction in society.…”
mentioning
confidence: 99%